Analisis Sektor Unggulan Kabupaten Mandailing Natal - Putri Ayuni Sari; Muhammad Yafiz; Reni Ria Armayani Hasibuan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study discusses the classification of economic sector growth, base and non-base sectors, leading sectors in Mandailing Natal Regency. The purpose of this study is to determine the leading sectors that can be developed (superior) in Mandailing Natal Regency in 2017-2021 as a consideration in preparing economic development planning to accelerate economic growth and improve the welfare of the people of Mandailing Natal Regency. The analysis of this study relates to the field of regional economics. Therefore, the approach taken is theories related to regional economic development, regional economic planning, leading sectors and criteria for determining leading sectors, economic base theory, and Gross Regional Domestic Product (GRDP). This study used secondary data in the form of Gross Regional Domestic Product (GRDP) on the basis of current prices (ADHB) and on the basis of constant prices (ADHK) Mandailing Natal Regency in 2017-2021. The analysis tools used in completing this research are Klassen typology analysis, Location Quotient analysis, Shift Share Analysis. Based on the results of the average classification of economic sector growth Klassen typology which is a developed and rapidly growing sector in Mandailing Natal is the Agriculture, Forestry, and fisheries sectors. The average result of Location Quotient calculation which is the base sector is agriculture, forestry, and Fisheries. The results of Shift Share analysis show that the sector is competitive and has competitiveness, namely the Agriculture, Forestry, and fisheries sectors.